Analisis Manajemen Laba dengan Modified Jones Model Dalam Initial Public Offering (IPO) Perusahaan Manufaktur di Bursa Efek Indonesia - Nurrofiah, Nisa; Suryanto, Suryanto; Dai, Ratna Meisa (Journal of Business and Economics Research (JBE), 2024)
The purpose of this study is to identify instances of earnings management that manufacturing companies engage in between 2018 and 2020, when they first list their shares on the Indonesia Stock Exchange (IPO). This study employed a quantitative approach using a descriptive research design. The data in the research is secondary data consisting of financial reports for a period of two years before the IPO, at the time of the IPO, and two years after the IPO sourced from the official website of the Indonesia Stock Exchange and the company's website. In this study, 43 manufacturing enterprises that carried out an initial public offering (IPO) between 2018 and 2020 make up the research population. This study selected 41 manufacturing enterprises that satisfied the intended sample requirements by using purposive sampling techniques. The data analysis technique used in this research is the management detection method using the modified jones model and hypothesis testing using the Wilcoxon signed test. This research shows the results that there is a significant difference in the value of discretionary accruals during and after the IPO so that the hypothesis test shows that manufacturing companies that carry out initial public offerings (IPO) in the 2018-2020 period practice earnings management. Sample companies tend to carry out income maximization with the aim of reporting good performance or to cover declining profits. Meanwhile, the income minimization pattern is carried out to avoid or minimize company costs.